2014
DOI: 10.1097/icl.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Reshaping and Wavefront Aberrations During Overnight Orthokeratology

Abstract: Overnight OK caused unique changes in corneal thickness profiles at the vertical and horizontal meridians and increased corneal and ocular HOAs related to corneal reshaping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 37 publications
6
52
0
Order By: Relevance
“…Orthokeratology produces a significant increase in on‐axis HOAs, even after one night of wear . Following seven nights of treatment, the increase in corneal HOAs ranges from 0.199 μm over a 5 mm pupil, to 0.71 μm over a 6 mm pupil . Additionally, the increase in ocular HOAs has been reported to be 0.175 μm over a 5 mm pupil to 0.63 μm over a 6.5 mm pupil, with the changes in ocular and corneal HOAs typically stabilising after 30 nights of lens wear .…”
Section: Hoas and Myopia Control Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthokeratology produces a significant increase in on‐axis HOAs, even after one night of wear . Following seven nights of treatment, the increase in corneal HOAs ranges from 0.199 μm over a 5 mm pupil, to 0.71 μm over a 6 mm pupil . Additionally, the increase in ocular HOAs has been reported to be 0.175 μm over a 5 mm pupil to 0.63 μm over a 6.5 mm pupil, with the changes in ocular and corneal HOAs typically stabilising after 30 nights of lens wear .…”
Section: Hoas and Myopia Control Interventionsmentioning
confidence: 99%
“…Additionally, the increase in ocular HOAs has been reported to be 0.175 μm over a 5 mm pupil to 0.63 μm over a 6.5 mm pupil, with the changes in ocular and corneal HOAs typically stabilising after 30 nights of lens wear . The predominant changes in HOAs are positive shifts in corneal and ocular primary spherical aberration (Z40), and corneal and ocular primary horizontal coma (Z31). In addition, changes in corneal primary vertical coma (Z31) have been reported .…”
Section: Hoas and Myopia Control Interventionsmentioning
confidence: 99%
“…Previous studies have reported flattened corneal curvature, [2,3] reduced central corneal thickness (CCT), and increased thickness in the mid-peripheral cornea after orthokeratology. [4,5] There are also studies showing a thinned central epithelial layer [6,7] and thickened corneal stromal layer [8,9] after wearing orthokeratology lens.…”
Section: Introductionmentioning
confidence: 99%
“…As the corneal shape is altered during orthokeratology treatment, both corneal and ocular aberrations, primarily spherical and comatic aberrations, significantly increase . Hiraoka et al investigated the correlations between ocular aberrations and axial elongation in 55 children (mean age: 10.3 ± 1.4 years) undergoing orthokeratology treatment for one year and showed that children with greater increases in the root‐mean‐square (RMS) error values for spherical, comatic, and total higher‐order aberrations (HOAs) exhibited slower axial eye growth.…”
mentioning
confidence: 99%